Pengaruh Motivasi, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT IDK Adam Malik Medan - Putri Asa; Seraphina Damayanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This lstudy laims lto lanalyze lthe limpact lof lmotivation, lwork ldiscipline land lwork lenvironment lon lemployee lperformance latlPT lIDK lAdam lMalik lMedan. lThe lpopulation lis l235 lpeople land lthe lsample lin lthis lstudy lis l148 lpeople. lTesting lusinglmultiple llinear lanalysis ltechniques lpartial lhypothesis ltest lresults lobtained lthat lmotivation lhas la lvalue lof ltcount> lttablelthat lis l3.771> l1.65521 lwith la lsignificant llevel lof l0.000 l<0.05, lwork ldiscipline lhas la lvalue lof ltcount> lttable lthat lis l6.177>l1.65521 lwith la lsignificant llevel l0.000 l<0.05 land lthe lwork lenvironment lhas la lvalue lof ltcount> lttable lthat lis l4.184 l>l1.65521 lwith la lsignificant llevel lof l0.000 l<0.05 lso lthat lmotivation, lwork ldiscipline land lwork lenvironment lhave la lpositiveland lsignificant leffect lon lemployee lperformance lat lPT lIDK lAdam lMalik lMedan. lSimultaneous ltest lresults lobtained lthat lthelvalue lof lFcount l> lFtable lof l135,077> l2.67 lwith la lsignificant llevel lof l0.000 l<0.05 lso lthat lit lcan lbe lconcluded lthatlmotivation, lwork ldiscipline land lwork lenvironment lhave la lsignificant land ljoint leffect lon lemployee lperformance lat lPT lIDKlAdam lMalik. lMedan. lObtaining lthe lcoefficient lof ldetermination ltest lobtained lan ladjusted lr lsquare lvalue lof l0.732 lorl73.2% lwhich lmeans lthat lmotivation, lwork ldiscipline land lwork lenvironment lonly lexplain lvariations lin lteacherlperformance lvariables lby l73.2% land lthe lremaining l26.8% lis linfluenced lby lother lvariables loutside lthe lvariable. lthislresearch. Keywords: Motivation, Work Discipline, Work Environment, Employee Performance